2011
DOI: 10.1089/dna.2010.1048
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Characterization of Rat Transmembrane Protein 225 Specifically Expressed in Testis

Abstract: Testis is the one and only location of spermatogenesis and sexual hormone production. Spermatogenesis is a complicated physiological process regulated by many genes specifically and differentially expressed in the testis. In this study, Transmembrane Protein 225 (TMEM225), which is specifically expressed in rat testis, has been identified. TMEM225 was cloned from the testis cDNA library and was mapped to chromosome 8q22 by browsing the University of California Santa Cruz genomic database. It contains an open r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The expression profile of Tmem225 in the testis was first reported in rats by Yang et al (2011). They reported that Tmem225 is expressed only after 13 months, concluding that Tmem225 is an age-related gene that may not play a role in the first wave of spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression profile of Tmem225 in the testis was first reported in rats by Yang et al (2011). They reported that Tmem225 is expressed only after 13 months, concluding that Tmem225 is an age-related gene that may not play a role in the first wave of spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Since the activity and substrate specificity of the PP1 catalytic subunit are defined by various regulatory proteins expressed in a spatially and temporally‐specific manner (Cohen and Cohen ), we hypothesized that TMEM225 may regulate PP1 activity in male germ cells. Recently, Yang et al reported that Tmem225 mRNA is specifically expressed in the rat testis after 13 months of age, and is enriched in spermatocytes and round‐spermatids (Yang et al, ). The TMEM225 protein profile, however, has not been investigated in the testes, nor has its relationship to PP1γ2 been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 To date, many testis-specific genes have been identified in mice, for example, Srg4, 9,10 Spergen-1, 11 Samp32, 12 Fank1, 13 Tsga10, 14 and Tmem225. 15 Many reports have demonstrated that about 4% of the mouse genome was dedicated to testisspecific transcripts. 16 In recent years, some research have characterized the expression profiles of many genes in mouse testes using high-throughput gene expression profiling, 17 and a number of novel testis-specific genes were identified and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 To date, many testis-specific genes have been identified in mice, for example, Srg4 , 9,10 Spergen-1 , 11 Samp32 , 12 Fank1 , 13 Tsga10 , 14 and Tmem225 . 15 Many reports have demonstrated that about 4% of the mouse genome was dedicated to testis-specific transcripts. 16…”
Section: Introductionmentioning
confidence: 99%
“…During spermiogenesis, the round spermatids undergo dramatic morphological and cellular changes, including formation of the acrosome, elongation and condensation of the nucleus, formation of the flagellum, and disposal of unnecessary cytoplasm, to produce highly specialized and polarized spermatozoa (Hecht 1998). Though many genes have been discovered and confirmed to be related to spermatogenesis (Liu et al 2004;Mu et al 2006;Yang et al 2011b), there are still many unidentified and uncharacterized genes and, most importantly, it remains to be clarified how spermatogenesis is controlled and regulated by these genes and their interactions (Eddy 2002;Poongothai et al 2009;Zheng et al 2010). Thus, further research on novel genes and investigation of their functions is crucial to help us elucidate the mechanisms of spermatogenesis and the underlying gene network.…”
Section: Introductionmentioning
confidence: 99%